2013
DOI: 10.1007/s00330-013-2835-9
|View full text |Cite
|
Sign up to set email alerts
|

Whole-body MRI for the detection of bone marrow involvement in lymphoma: prospective study in 116 patients and comparison with FDG-PET

Abstract: • Bone marrow involvement in lymphoma has prognostic and therapeutic implications. • Blind bone marrow biopsy (BMB) is standard for bone marrow assessment. • Neither whole-body MRI nor FDG-PET can yet replace BMB. • Both techniques have higher sensitivity in aggressive than in indolent lymphoma. • Both imaging techniques are complementary to BMB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 26 publications
1
37
0
2
Order By: Relevance
“…In addition, several studies have shown that WB-MRI equals or betters CT in lymphoma staging [30,31], suggesting it be used in place of CT. Both WB-MRI and 18 F-FDG-PET/CT have been shown to be reliable tools for the detection of bone marrow involvement in patients with lymphoma [32,33]. In this setting, both techniques seem to have distinct diagnostic accuracy in aggressive lymphomas, showing reduced sensitivity for the detection of low-volume bone marrow involvement in i-NHLs, where imaging modalities are complementary to bone marrow biopsy [32,33].…”
Section: Imaging Monitoring and Wwmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, several studies have shown that WB-MRI equals or betters CT in lymphoma staging [30,31], suggesting it be used in place of CT. Both WB-MRI and 18 F-FDG-PET/CT have been shown to be reliable tools for the detection of bone marrow involvement in patients with lymphoma [32,33]. In this setting, both techniques seem to have distinct diagnostic accuracy in aggressive lymphomas, showing reduced sensitivity for the detection of low-volume bone marrow involvement in i-NHLs, where imaging modalities are complementary to bone marrow biopsy [32,33].…”
Section: Imaging Monitoring and Wwmentioning
confidence: 99%
“…Both WB-MRI and 18 F-FDG-PET/CT have been shown to be reliable tools for the detection of bone marrow involvement in patients with lymphoma [32,33]. In this setting, both techniques seem to have distinct diagnostic accuracy in aggressive lymphomas, showing reduced sensitivity for the detection of low-volume bone marrow involvement in i-NHLs, where imaging modalities are complementary to bone marrow biopsy [32,33]. In fact, bone marrow biopsy is still recommended in NHL [15], being essential for both diagnosis and evaluation of marrow cellularity and hematopoietic reserve [34][35][36], while it is no longer required for Hodgkin's lymphoma [15].…”
Section: Imaging Monitoring and Wwmentioning
confidence: 99%
“…Their recent paper cited in their letter provides interesting results about the comparable performance of whole-body MR imaging and 18 F-FDG PET/CT for detection of bone marrow involvement in a mixed population of patients with newly diagnosed low-, intermediate-, and high-grade lymphoma (2). We agree with Adams et al that the potential role of whole-body MR imaging for evaluation of lymphomatous bone marrow involvement in comparison or in association with 18 F-FDG PET/CT needs to be further explored.…”
Section: Replymentioning
confidence: 99%
“…In a multivariate analysis, Berthet et al showed that only the International Prognostic Index (IPI) and the 18 F-FDG PET bone marrow status were independent predictors of progression-free survival (P 5 0.005 and P 5 0.02, respectively), whereas only the IPI remained an independent predictor of overall survival (P 5 0.004). Almost simultaneously, another study on the same subject was published by Khan et al (2). In their retrospective study that included 130 patients with newly diagnosed DLBCL, 35 were judged to have marrow involvement; of these, 33 were identified by 18 F-FDG PET and 14 by bone marrow biopsy.…”
mentioning
confidence: 95%